How Parents' Academic Background Can Affect Parental Involvement in Preschooler's Education - Handayani, Dewa Ayu Puteri; Magta, Mutiara; Wirabrata, Dewa Gede Firstia (Universitas Pendidikan Ganesha, 2020)
Parental involvement in children education has been acknowledged to bring about many advantages to children education, especially in boosting children’s academic performance at school. This study is aimed at revealing the effect of parents’ educational level on parental efforts to facilitate the learning of their children. It is a quantitative research in which the samples were 230 parents whom their children were admitted in fifteen early childhood education institutions in Buleleng Regency, Bali Indonesia. Data were collected using Family Involvement Questionnaires-Short Form (FIQ-SF) developed by Fantuzzo et al. (2013) which had been translated and adapted to Indonesian context. Data were analyzed using Independent Sample T-test technique. The results demonstrated that parents who are well educated exhibit higher level of involvement in their children education compared to less educated parents, especially in home-based involvement and home-school conferencing, but not in school-based involvement. The reasons of this result and the direction for future research were discussed in this study. Keywords: parental involvement, early childhood education, education, preschooler